Copy number variants and fixed duplications among 198 rhesus macaques (Macaca mulatta). - Brasó-Vives, Marina; Povolotskaya, Inna S; Hartasánchez, Diego A; Farré, Xavier; Fernandez-Callejo, Marcos; Raveendran, Muthuswamy; Harris, R Alan; Rosene, Douglas L; Lorente-Galdos, Belen; Navarro, Arcadi; Marques-Bonet, Tomas; Rogers, Jeffrey; et al. (PLoS Genet, 2020)
The rhesus macaque is an abundant species of Old World monkeys and a valuable model organism for biomedical research due to its close phylogenetic relationship to humans. Copy number variation is one of the main sources of genomic diversity within and between species and a widely recognized cause of inter-individual differences in disease risk. However, copy number differences among rhesus macaques and between the human and macaque genomes, as well as the relevance of this diversity to research involving this nonhuman primate, remain understudied. Here we present a high-resolution map of sequence copy number for the rhesus macaque genome constructed from a dataset of 198 individuals. Our results show that about one-eighth of the rhesus macaque reference genome is composed of recently duplicated regions, either copy number variable regions or fixed duplications. Comparison with human genomic copy number maps based on previously published data shows that, despite overall similarities in the genome-wide distribution of these regions, there are specific differences at the chromosome level. Some of these create differences in the copy number profile between human disease genes and their rhesus macaque orthologs. Our results highlight the importance of addressing the number of copies of target genes in the design of experiments and cautions against human-centered assumptions in research conducted with model organisms. Overall, we present a genome-wide copy number map from a large sample of rhesus macaque individuals representing an important novel contribution concerning the evolution of copy number in primate genomes.
Keywords: Animals; Chromosome Mapping; DNA Copy Number Variations; Female; Gene Duplication; Genetics, Population; Genome; High-Throughput Nucleotide Sequencing; Humans; Macaca mulatta; Male; Open Reading Frames; Phylogeny; Sequence Analysis, DNA; Species Specificity

Major Impacts of Widespread Structural Variation on Gene Expression and Crop Improvement in Tomato. - Alonge, Michael; Wang, Xingang; Benoit, Matthias; Soyk, Sebastian; Pereira, Lara; Zhang, Lei; Suresh, Hamsini; Ramakrishnan, Srividya; Maumus, Florian; Ciren, Danielle; Levy, Yuval; Harel, Tom Hai; et al. (Cell, 2020)
Structural variants (SVs) underlie important crop improvement and domestication traits. However, resolving the extent, diversity, and quantitative impact of SVs has been challenging. We used long-read nanopore sequencing to capture 238,490 SVs in 100 diverse tomato lines. This panSV genome, along with 14 new reference assemblies, revealed large-scale intermixing of diverse genotypes, as well as thousands of SVs intersecting genes and cis-regulatory regions. Hundreds of SV-gene pairs exhibit subtle and significant expression changes, which could broadly influence quantitative trait variation. By combining quantitative genetics with genome editing, we show how multiple SVs that changed gene dosage and expression levels modified fruit flavor, size, and production. In the last example, higher order epistasis among four SVs affecting three related transcription factors allowed introduction of an important harvesting trait in modern tomato. Our findings highlight the underexplored role of SVs in genotype-to-phenotype relationships and their widespread importance and utility in crop improvement.
Keywords: Alleles; Crops, Agricultural; Cytochrome P-450 Enzyme System; Ecotype; Epistasis, Genetic; Fruit; Gene Duplication; Gene Expression Regulation, Plant; Genome, Plant; Genomic Structural Variation; Genotype; Inbreeding; Lycopersicon esculentum; Molecular Sequence Annotation; Phenotype; Plant Breeding; Quantitative Trait Loci

Rapid, Paralog-Sensitive CNV Analysis of 2457 Human Genomes Using QuicK-mer2. - Shen, Feichen; Kidd, Jeffrey M (Genes (Basel), 2020)
Gene duplication is a major mechanism for the evolution of gene novelty, and copy-number variation makes a major contribution to inter-individual genetic diversity. However, most approaches for studying copy-number variation rely upon uniquely mapping reads to a genome reference and are unable to distinguish among duplicated sequences. Specialized approaches to interrogate specific paralogs are comparatively slow and have a high degree of computational complexity, limiting their effective application to emerging population-scale data sets. We present QuicK-mer2, a self-contained, mapping-free approach that enables the rapid construction of paralog-specific copy-number maps from short-read sequence data. This approach is based on the tabulation of unique k-mer sequences from short-read data sets, and is able to analyze a 20X coverage human genome in approximately 20 min. We applied our approach to newly released sequence data from the 1000 Genomes Project, constructed paralog-specific copy-number maps from 2457 unrelated individuals, and uncovered copy-number variation of paralogous genes. We identify nine genes where none of the analyzed samples have a copy number of two, 92 genes where the majority of samples have a copy number other than two, and describe rare copy number variation effecting multiple genes at the APOBEC3 locus.
Keywords: Algorithms; Computational Biology; DNA Copy Number Variations; Evolution, Molecular; Gene Duplication; Genome, Human; Humans; Sequence Analysis, DNA

Recurrent De Novo NAHR Reciprocal Duplications in the ATAD3 Gene Cluster Cause a Neurogenetic Trait with Perturbed Cholesterol and Mitochondrial Metabolism. - Gunning, Adam C; Strucinska, Klaudia; Muñoz Oreja, Mikel; Parrish, Andrew; Caswell, Richard; Stals, Karen L; Durigon, Romina; Durlacher-Betzer, Karina; Cunningham, Mitchell H; Grochowski, Christopher M; Baptista, Julia; Tysoe, Carolyn; et al. (Am J Hum Genet, 2020)
Recent studies have identified both recessive and dominant forms of mitochondrial disease that result from ATAD3A variants. The recessive form includes subjects with biallelic deletions mediated by non-allelic homologous recombination. We report five unrelated neonates with a lethal metabolic disorder characterized by cardiomyopathy, corneal opacities, encephalopathy, hypotonia, and seizures in whom a monoallelic reciprocal duplication at the ATAD3 locus was identified. Analysis of the breakpoint junction fragment indicated that these 67 kb heterozygous duplications were likely mediated by non-allelic homologous recombination at regions of high sequence identity in ATAD3A exon 11 and ATAD3C exon 7. At the recombinant junction, the duplication allele produces a fusion gene derived from ATAD3A and ATAD3C, the protein product of which lacks key functional residues. Analysis of fibroblasts derived from two affected individuals shows that the fusion gene product is expressed and stable. These cells display perturbed cholesterol and mitochondrial DNA organization similar to that observed for individuals with severe ATAD3A deficiency. We hypothesize that the fusion protein acts through a dominant-negative mechanism to cause this fatal mitochondrial disorder. Our data delineate a molecular diagnosis for this disorder, extend the clinical spectrum associated with structural variation at the ATAD3 locus, and identify a third mutational mechanism for ATAD3 gene cluster variants. These results further affirm structural variant mutagenesis mechanisms in sporadic disease traits, emphasize the importance of copy number analysis in molecular genomic diagnosis, and highlight some of the challenges of detecting and interpreting clinically relevant rare gene rearrangements from next-generation sequencing data.
Keywords: Amino Acid Sequence; ATPases Associated with Diverse Cellular Activities; Brain Diseases; Cardiomyopathies; Cholesterol; Corneal Opacity; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Homologous Recombination; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Diseases; Mitochondrial Proteins; Muscle Hypotonia; Mutation; Protein Conformation; Seizures; Sequence Homology

Recurrent Rare Copy Number Variants Increase Risk for Esotropia. - Whitman, Mary C; Di Gioia, Silvio Alessandro; Chan, Wai-Man; Gelber, Alon; Pratt, Brandon M; Bell, Jessica L; Collins, Thomas E; Knowles, James A; Armoskus, Christopher; Pato, Michele; Pato, Carlos; Shaaban, Sherin; et al. (Invest Ophthalmol Vis Sci, 2020)
Purpose: To determine whether rare copy number variants (CNVs) increase risk for comitant esotropia. Methods: CNVs were identified in 1614 Caucasian individuals with comitant esotropia and 3922 Caucasian controls from Illumina SNP genotyping using two Hidden Markov model (HMM) algorithms, PennCNV and QuantiSNP, which call CNVs based on logR ratio and B allele frequency. Deletions and duplications greater than 10 kb were included. Common CNVs were excluded. Association testing was performed with 1 million permutations in PLINK. Significant CNVs were confirmed with digital droplet polymerase chain reaction (ddPCR). Whole genome sequencing was performed to determine insertion location and breakpoints. Results: Esotropia patients have similar rates and proportions of CNVs compared with controls but greater total length and average size of both deletions and duplications. Three recurrent rare duplications significantly (P = 1 × 10-6) increase the risk of esotropia: chromosome 2p11.2 (hg19, 2:87428677-87965359), spanning one long noncoding RNA (lncRNA) and two microRNAs (OR 14.16; 95% confidence interval [CI] 5.4-38.1); chromosome 4p15.2 (hg19, 4:25554332-25577184), spanning one lncRNA (OR 11.1; 95% CI 4.6-25.2); chromosome 10q11.22 (hg19, 10:47049547-47703870) spanning seven protein-coding genes, one lncRNA, and four pseudogenes (OR 8.96; 95% CI 5.4-14.9). Overall, 114 cases (7%) and only 28 controls (0.7%) had one of the three rare duplications. No case nor control had more than one of these three duplications. Conclusions: Rare CNVs are a source of genetic variation that contribute to the genetic risk for comitant esotropia, which is likely polygenic. Future research into the functional consequences of these recurrent duplications may shed light on the pathophysiology of esotropia.
Keywords: Case-Control Studies; DNA Copy Number Variations; Esotropia; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Infant; Male; Markov Chains; Polymerase Chain Reaction; Risk Factors

Predicting human genes susceptible to genomic instability associated with /-mediated rearrangements. - Song, Xiaofei; Beck, Christine R; Du, Renqian; Campbell, Ian M; Coban-Akdemir, Zeynep; Gu, Shen; Breman, Amy M; Stankiewicz, Pawel; Ira, Grzegorz; Shaw, Chad A; Lupski, James R (Genome Res, 2018)
elements, the short interspersed element numbering more than 1 million copies per human genome, can mediate the formation of copy number variants (CNVs) between substrate pairs. These /-mediated rearrangements (AAMRs) can result in pathogenic variants that cause diseases. To investigate the impact of AAMR on gene variation and human health, we first characterized s that are involved in mediating CNVs (CNV-s) and observed that these s tend to be evolutionarily younger. We then computationally generated, with the assistance of a supercomputer, a test data set consisting of 78 million pairs and predicted ∼18% of them are potentially susceptible to AAMR. We further determined the relative risk of AAMR in 12,074 OMIM genes using the count of predicted CNV- pairs and experimentally validated the predictions with 89 samples selected by correlating predicted hotspots with a database of CNVs identified by clinical chromosomal microarrays (CMAs) on the genomes of approximately 54,000 subjects. We fine-mapped 47 duplications, 40 deletions, and two complex rearrangements and examined a total of 52 breakpoint junctions of simple CNVs. Overall, 94% of the candidate breakpoints were at least partially mediated. We successfully predicted all (100%) of pairs that mediated deletions ( = 21) and achieved an 87% positive predictive value overall when including AAMR-generated deletions and duplications. We provided a tool, AluAluCNVpredictor, for assessing AAMR hotspots and their role in human disease. These results demonstrate the utility of our predictive model and provide insights into the genomic features and molecular mechanisms underlying AAMR.
Keywords: Alu Elements; DNA Copy Number Variations; Gene Duplication; Genome, Human; Genomic Instability; Humans; Sequence Deletion

Efficient CNV breakpoint analysis reveals unexpected structural complexity and correlation of dosage-sensitive genes with clinical severity in genomic disorders. - Zhang, Ling; Wang, Jingmin; Zhang, Cheng; Li, Dongxiao; Carvalho, Claudia M B; Ji, Haoran; Xiao, Jianqiu; Wu, Ye; Zhou, Weichen; Wang, Hongyan; Jin, Li; Luo, Yang; et al. (Hum Mol Genet, 2017)
Genomic disorders are the clinical conditions manifested by submicroscopic genomic rearrangements including copy number variants (CNVs). The CNVs can be identified by array-based comparative genomic hybridization (aCGH), the most commonly used technology for molecular diagnostics of genomic disorders. However, clinical aCGH only informs CNVs in the probe-interrogated regions. Neither orientational information nor the resulting genomic rearrangement structure is provided, which is a key to uncovering mutational and pathogenic mechanisms underlying genomic disorders. Long-range polymerase chain reaction (PCR) is a traditional approach to obtain CNV breakpoint junction, but this method is inefficient when challenged by structural complexity such as often found at the PLP1 locus in association with Pelizaeus-Merzbacher disease (PMD). Here we introduced 'capture and single-molecule real-time sequencing' (cap-SMRT-seq) and newly developed 'asymmetry linker-mediated nested PCR walking' (ALN-walking) for CNV breakpoint sequencing in 49 subjects with PMD-associated CNVs. Remarkably, 29 (94%) of the 31 CNV breakpoint junctions unobtainable by conventional long-range PCR were resolved by cap-SMRT-seq and ALN-walking. Notably, unexpected CNV complexities, including inter-chromosomal rearrangements that cannot be resolved by aCGH, were revealed by efficient breakpoint sequencing. These sequence-based structures of PMD-associated CNVs further support the role of DNA replicative mechanisms in CNV mutagenesis, and facilitate genotype-phenotype correlation studies. Intriguingly, the lengths of gained segments by CNVs are strongly correlated with clinical severity in PMD, potentially reflecting the functional contribution of other dosage-sensitive genes besides PLP1. Our study provides new efficient experimental approaches (especially ALN-walking) for CNV breakpoint sequencing and highlights their importance in uncovering CNV mutagenesis and pathogenesis in genomic disorders.
Keywords: Base Sequence; Comparative Genomic Hybridization; DNA Copy Number Variations; DNA Replication; Female; Gene Dosage; Gene Duplication; Gene Rearrangement; Genetic Association Studies; Genome, Human; Genomics; Humans; Male; Mutation; Pelizaeus-Merzbacher Disease; Sequence Analysis, DNA

Chimeric transcripts resulting from complex duplications in chromosome Xq28. - Zuccherato, Luciana W; Alleva, Benjamin; Whiters, Marjorie A; Carvalho, Claudia M B; Lupski, James R (Hum Genet, 2016)
Gene fusions have been observed in somatic alterations in cancer and in schizophrenia. However, the underlying mechanism(s) for their formation are poorly understood. We experimentally demonstrated the expression of splicing variants of in silico predicted chimeric genes F8/CSAG1 and BCAP31/TEX28 in two individuals with de novo complex genomic rearrangements of Xq28; F8/CSAG1 includes exonization of an ERVL-MaLR intronic repetitive element. We provide evidence that replicative repair may contribute to exon shuffling processes and diversify the repertoire of expressed transcripts.
Keywords: Antigens, Neoplasm; Base Sequence; Cell Line; Chromosomes, Human, X; Exons; Gene Duplication; Gene Expression Regulation; Gene Rearrangement; Humans; Introns; Male; Membrane Proteins; Molecular Sequence Data; Neoplasm Proteins; RNA Splicing; RNA, Messenger; Transcription, Genetic

Germline or somatic GPR101 duplication leads to X-linked acrogigantism: a clinico-pathological and genetic study. - Iacovazzo, Donato; Caswell, Richard; Bunce, Benjamin; Jose, Sian; Yuan, Bo; Hernández-Ramírez, Laura C; Kapur, Sonal; Caimari, Francisca; Evanson, Jane; Ferraù, Francesco; Dang, Mary N; Gabrovska, Plamena; et al. (Acta Neuropathol Commun, 2016)
Non-syndromic pituitary gigantism can result from AIP mutations or the recently identified Xq26.3 microduplication causing X-linked acrogigantism (XLAG). Within Xq26.3, GPR101 is believed to be the causative gene, and the c.924G > C (p.E308D) variant in this orphan G protein-coupled receptor has been suggested to play a role in the pathogenesis of acromegaly.We studied 153 patients (58 females and 95 males) with pituitary gigantism. AIP mutation-negative cases were screened for GPR101 duplication through copy number variation droplet digital PCR and high-density aCGH. The genetic, clinical and histopathological features of XLAG patients were studied in detail. 395 peripheral blood and 193 pituitary tumor DNA samples from acromegaly patients were tested for GPR101 variants.We identified 12 patients (10 females and 2 males; 7.8 %) with XLAG. In one subject, the duplicated region only contained GPR101, but not the other three genes in found to be duplicated in the previously reported patients, defining a new smallest region of overlap of duplications. While females presented with germline mutations, the two male patients harbored the mutation in a mosaic state. Nine patients had pituitary adenomas, while three had hyperplasia. The comparison of the features of XLAG, AIP-positive and GPR101&AIP-negative patients revealed significant differences in sex distribution, age at onset, height, prolactin co-secretion and histological features. The pathological features of XLAG-related adenomas were remarkably similar. These tumors had a sinusoidal and lobular architecture. Sparsely and densely granulated somatotrophs were admixed with lactotrophs; follicle-like structures and calcifications were commonly observed. Patients with sporadic of familial acromegaly did not have an increased prevalence of the c.924G > C (p.E308D) GPR101 variant compared to public databases.In conclusion, XLAG can result from germline or somatic duplication of GPR101. Duplication of GPR101 alone is sufficient for the development of XLAG, implicating it as the causative gene within the Xq26.3 region. The pathological features of XLAG-associated pituitary adenomas are typical and, together with the clinical phenotype, should prompt genetic testing.
Keywords: Acromegaly; Adenoma; Adolescent; Child; Child, Preschool; Female; Gene Duplication; Germ-Line Mutation; Gigantism; Humans; Infant; Intracellular Signaling Peptides and Proteins; Male; Pituitary Neoplasms; Receptors, G-Protein-Coupled; Treatment Outcome; Young Adult

Alu-mediated diverse and complex pathogenic copy-number variants within human chromosome 17 at p13.3. - Gu, Shen; Yuan, Bo; Campbell, Ian M; Beck, Christine R; Carvalho, Claudia M B; Nagamani, Sandesh C S; Erez, Ayelet; Patel, Ankita; Bacino, Carlos A; Shaw, Chad A; Stankiewicz, Paweł; Cheung, Sau Wai; et al. (Hum Mol Genet, 2015)
Alu repetitive elements are known to be major contributors to genome instability by generating Alu-mediated copy-number variants (CNVs). Most of the reported Alu-mediated CNVs are simple deletions and duplications, and the mechanism underlying Alu-Alu-mediated rearrangement has been attributed to non-allelic homologous recombination (NAHR). Chromosome 17 at the p13.3 genomic region lacks extensive low-copy repeat architecture; however, it is highly enriched for Alu repetitive elements, with a fraction of 30% of total sequence annotated in the human reference genome, compared with the 10% genome-wide and 18% on chromosome 17. We conducted mechanistic studies of the 17p13.3 CNVs by performing high-density oligonucleotide array comparative genomic hybridization, specifically interrogating the 17p13.3 region with ∼150 bp per probe density; CNV breakpoint junctions were mapped to nucleotide resolution by polymerase chain reaction and Sanger sequencing. Studied rearrangements include 5 interstitial deletions, 14 tandem duplications, 7 terminal deletions and 13 complex genomic rearrangements (CGRs). Within the 17p13.3 region, Alu-Alu-mediated rearrangements were identified in 80% of the interstitial deletions, 46% of the tandem duplications and 50% of the CGRs, indicating that this mechanism was a major contributor for formation of breakpoint junctions. Our studies suggest that Alu repetitive elements facilitate formation of non-recurrent CNVs, CGRs and other structural aberrations of chromosome 17 at p13.3. The common observation of Alu-mediated rearrangement in CGRs and breakpoint junction sequences analysis further demonstrates that this type of mechanism is unlikely attributed to NAHR, but rather may be due to a recombination-coupled DNA replicative repair process.
Keywords: Alleles; Alu Elements; Base Sequence; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Rearrangement; Genome, Human; Genomic Instability; Genomics; Homologous Recombination; Humans; Male; Molecular Sequence Data; Segmental Duplications, Genomic; Sequence Deletion

Complex genomic rearrangements at the PLP1 locus include triplication and quadruplication. - Beck, Christine R; Carvalho, Claudia M B; Banser, Linda; Gambin, Tomasz; Stubbolo, Danielle; Yuan, Bo; Sperle, Karen; McCahan, Suzanne M; Henneke, Marco; Seeman, Pavel; Garbern, James Y; Hobson, Grace M; et al. (PLoS Genet, 2015)
Inverted repeats (IRs) can facilitate structural variation as crucibles of genomic rearrangement. Complex duplication-inverted triplication-duplication (DUP-TRP/INV-DUP) rearrangements that contain breakpoint junctions within IRs have been recently associated with both MECP2 duplication syndrome (MIM#300260) and Pelizaeus-Merzbacher disease (PMD, MIM#312080). We investigated 17 unrelated PMD subjects with copy number gains at the PLP1 locus including triplication and quadruplication of specific genomic intervals-16/17 were found to have a DUP-TRP/INV-DUP rearrangement product. An IR distal to PLP1 facilitates DUP-TRP/INV-DUP formation as well as an inversion structural variation found frequently amongst normal individuals. We show that a homology-or homeology-driven replicative mechanism of DNA repair can apparently mediate template switches within stretches of microhomology. Moreover, we provide evidence that quadruplication and potentially higher order amplification of a genomic interval can occur in a manner consistent with rolling circle amplification as predicted by the microhomology-mediated break induced replication (MMBIR) model.
Keywords: Chromosome Breakpoints; Chromosome Inversion; Gene Dosage; Gene Duplication; Humans; Myelin Proteolipid Protein; Pelizaeus-Merzbacher Disease

Nonrecurrent 17p11.2p12 Rearrangement Events that Result in Two Concomitant Genomic Disorders: The PMP22-RAI1 Contiguous Gene Duplication Syndrome. - Yuan, Bo; Harel, Tamar; Gu, Shen; Liu, Pengfei; Burglen, Lydie; Chantot-Bastaraud, Sandra; Gelowani, Violet; Beck, Christine R; Carvalho, Claudia M B; Cheung, Sau Wai; Coe, Andrew; Malan, Valérie; et al. (Am J Hum Genet, 2015)
The genomic duplication associated with Potocki-Lupski syndrome (PTLS) maps in close proximity to the duplication associated with Charcot-Marie-Tooth disease type 1A (CMT1A). PTLS is characterized by hypotonia, failure to thrive, reduced body weight, intellectual disability, and autistic features. CMT1A is a common autosomal dominant distal symmetric peripheral polyneuropathy. The key dosage-sensitive genes RAI1 and PMP22 are respectively associated with PTLS and CMT1A. Recurrent duplications accounting for the majority of subjects with these conditions are mediated by nonallelic homologous recombination between distinct low-copy repeat (LCR) substrates. The LCRs flanking a contiguous genomic interval encompassing both RAI1 and PMP22 do not share extensive homology; thus, duplications encompassing both loci are rare and potentially generated by a different mutational mechanism. We characterized genomic rearrangements that simultaneously duplicate PMP22 and RAI1, including nine potential complex genomic rearrangements, in 23 subjects by high-resolution array comparative genomic hybridization and breakpoint junction sequencing. Insertions and microhomologies were found at the breakpoint junctions, suggesting potential replicative mechanisms for rearrangement formation. At the breakpoint junctions of these nonrecurrent rearrangements, enrichment of repetitive DNA sequences was observed, indicating that they might predispose to genomic instability and rearrangement. Clinical evaluation revealed blended PTLS and CMT1A phenotypes with a potential earlier onset of neuropathy. Moreover, additional clinical findings might be observed due to the extra duplicated material included in the rearrangements. Our genomic analysis suggests replicative mechanisms as a predominant mechanism underlying PMP22-RAI1 contiguous gene duplications and provides further evidence supporting the role of complex genomic architecture in genomic instability.
Keywords: Abnormalities, Multiple; Charcot-Marie-Tooth Disease; Child; Child, Preschool; Chromosome Disorders; Chromosome Duplication; Chromosomes, Human, Pair 17; Comparative Genomic Hybridization; Female; Follow-Up Studies; Gene Duplication; Gene Rearrangement; Genome, Human; Genomics; Humans; Infant; Male; Models, Genetic; Myelin Proteins; Phenotype; Prognosis; Recombination, Genetic; Transcription Factors

Rare A2ML1 variants confer susceptibility to otitis media. - Santos-Cortez, Regie Lyn P; Chiong, Charlotte M; Reyes-Quintos, Ma Rina T; Tantoco, Ma Leah C; Wang, Xin; Acharya, Anushree; Abbe, Izoduwa; Giese, Arnaud P; Smith, Joshua D; Allen, E Kaitlynn; Li, Biao; Cutiongco-de la Paz, Eva Maria; et al. (Nat Genet, 2015)
A duplication variant within the middle ear-specific gene A2ML1 cosegregates with otitis media in an indigenous Filipino pedigree (LOD score = 7.5 at reduced penetrance) and lies within a founder haplotype that is also shared by 3 otitis-prone European-American and Hispanic-American children but is absent in non-otitis-prone children and >62,000 next-generation sequences. We identified seven additional A2ML1 variants in six otitis-prone children. Collectively, our studies support a role for A2ML1 in the pathophysiology of otitis media.
Keywords: alpha-Macroglobulins; Animals; Base Sequence; Child; Cochlea; Exome; Family Health; Female; Gene Duplication; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Male; Mice, Inbred C57BL; Models, Molecular; Otitis Media; Pedigree; Principal Component Analysis; Protein Conformation; Sequence Analysis, DNA

Exonic duplication CNV of NDRG1 associated with autosomal-recessive HMSN-Lom/CMT4D. - Okamoto, Yuji; Goksungur, Meryem Tuba; Pehlivan, Davut; Beck, Christine R; Gonzaga-Jauregui, Claudia; Muzny, Donna M; Atik, Mehmed M; Carvalho, Claudia M B; Matur, Zeliha; Bayraktar, Serife; Boone, Philip M; Akyuz, Kaya; et al. (Genet Med, 2014)
PURPOSE: Copy-number variations as a mutational mechanism contribute significantly to human disease. Approximately one-half of the patients with Charcot-Marie-Tooth (CMT) disease have a 1.4 Mb duplication copy-number variation as the cause of their neuropathy. However, non-CMT1A neuropathy patients rarely have causative copy-number variations, and to date, autosomal-recessive disease has not been associated with copy-number variation as a mutational mechanism. METHODS: We performed Agilent 8 × 60 K array comparative genomic hybridization on DNA from 12 recessive Turkish families with CMT disease. Additional molecular studies were conducted to detect breakpoint junctions and to evaluate gene expression levels in a family in which we detected an intragenic duplication copy-number variation. RESULTS: We detected an ~6.25 kb homozygous intragenic duplication in NDRG1, a gene known to be causative for recessive HMSNL/CMT4D, in three individuals from a Turkish family with CMT neuropathy. Further studies showed that this intragenic copy-number variation resulted in a homozygous duplication of exons 6-8 that caused decreased mRNA expression of NDRG1. CONCLUSION: Exon-focused high-resolution array comparative genomic hybridization enables the detection of copy-number variation carrier states in recessive genes, particularly small copy-number variations encompassing or disrupting single genes. In families for whom a molecular diagnosis has not been elucidated by conventional clinical assays, an assessment for copy-number variations in known CMT genes might be considered.
Keywords: Adult; Base Sequence; Cell Cycle Proteins; Charcot-Marie-Tooth Disease; Comparative Genomic Hybridization; DNA Copy Number Variations; Female; Gene Duplication; Gene Expression; Genes, Recessive; Humans; Intracellular Signaling Peptides and Proteins; Male; Mutation; Refsum Disease; Sequence Analysis, DNA; Turkey; Young Adult